Diversity of Echinoderms in Balekambang Beach, Malang District, East Java - Buwono, Nanik Retno; Fitri, Nur Lailatul (El-Hayah : Jurnal Biologi, 2017)
Echinoderms is a component of biodiversity in the coral reefs. Echinoderms play an important role in ecosystem of coral reefs especially in food web, generally as predators and detritivors. This report aims to understand composition and density relative of fauna echinoderms on the Balekambang beach. The Transect line method were used and data retrieval was conducted at three stations. The result showed that echinoderms found in Balekambang beach consists of 7 species that are included in three classes, they were Phyllachantus imperialis, Tripneustes gratilla, Diadema setosum, Clypeaster reticulatus (Class Echinoidea), Archaster typicus (Class Asteroidea), Ophiotrix fragilis and Macrophiothrix belii (Class Ophiuroidea). The highest abundance of echinoderms on the station where located in the mangrove area which was dominated by Archaster typicus. The diversity of echinoderms on Balekambang beach were moderate category. The observations of chemical and physics parameters of the aquatic environment and the substrate obtained quite optimal for life of Echinoderms